LEGAL BASIS OF ACCESS TO ENVIRONMENTAL INFORMATION IN FOREST LEGISLATION OF UKRAINE - Проскура, Ганна Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The purpose of this article is to analyze regulatory and legal regulation of access to environmental information in the field of forestry legislation of Ukraine. The list of normative legal acts and international agreements in this field is determined. The methodological basis of the research comprise general scientific methods of scientific knowledge, such as integrated and interdisciplinary. Results: the main preconditions and needs of the implementation of the human right to environmental information in the forest sector are determined. Discussion: the basis of national and international forest legislation in the field of access to environmental information. It is common knowledge that forests are unique complex natural objects of great importance for the preservation of the environment and the maintenance of ecological balance. Preservation and reproduction of forests in Ukraine is one of the topical and problematic issues for today. One of the main aspects is the prevalence of economic interests over environmental ones. Huge damage to the forests is caused by fires, unauthorized deforestation, misuse of natural resources, pollution, etc. Forest law plays an important role in integration processes. To date, there is no effective mechanism for the implementation of access to information on forest resources and their state - fires, deforestation, etc. Therefore, we propose to consider in more detail the issue of access to environmental information in the process of transformation of forest legislation. We can conclude that the current forestry legislation in Ukraine needs to be rethought and improved. There is a need for detailed study, analysis of historical and contemporary experience of Ukraine and foreign countries, clear regulation of regulatory legal acts of Ukraine in this area. We consider it expedient to create a single electronic system containing data, including scientific, biological, ecological research and activities in the respective territories. In the context of European integration resources, we believe that the Environmental Law requires incorporation and codification.